Should Mannitol be Administered Orally and Intravenously in Hepatic Encephalopathy? - Andrei Vicentiu EDU; Alina DONCIU; Lucian NEGREANU (Modern Medicine)
Hepatic encephalopathy (HE) is a major neuropsychiatric complication in patients with liver diseases, significantly impacting survival rates and imposing substantial economic burdens. The severity of HE can be reduced and treated through the enteral and parenteral administration of mannitol, which acts on two important pathophysiological pathways: decreasing plasma ammonia levels and reducing cerebral edema.